Endobronchial and transbronchial biopsy experience: A United Kingdom survey. Issue 4 (24th April 2017) - Fallon, Janet; Medford, Andrew R.L.
Abstract : Background: Trainees are performing fewer bronchoscopies as a result of the increased use of endobronchial ultrasound‐guided transbronchial needle aspiration. Workforce planning and changes in trainee working patterns may also have compounded this situation. We investigated current trends in endobronchial biopsy (EBB) and transbronchial biopsy (TBB) training and competency in respiratory trainees and consultants across the United Kingdom. Methods: We performed a national survey and received 131 online responses from 58 consultants and 73 registrars across 13 United Kingdom deaneries. Results: A significant proportion (31%) of consultants, more than half of which were new consultants, had performed <500 bronchoscopies. Bronchoscopic biopsy experience varies widely across trainees and consultants (9.1% of senior trainees and 14.3% of new consultants had performed <100 bronchoscopies). Most trainees and some new consultants reported performing relatively low numbers of EBB (13% <20 and 52% <50 procedures) and TBB (75% of trainees, 36% of new consultants, 12% of established consultants <10 procedures). Significant numbers of trainees do not feel competent in EBB (24%) and TBB (89% of junior trainees, 64% of senior trainees) and some consultants (24% of new and established consultants) wish for support with TBB. Conclusions: These results have implications for future specialist training, curriculum planning, and service configuration. Training and performance of EBB and TBB may become concentrated in centers with an adequate volume of these procedures. Higher volumes of EBB and TBB may well be more likely to occur paradoxically in centers without endobronchial ultrasound‐guided transbronchial needle aspiration; however, this hypothesis requires further study.